Patterns of Human Resources Development on Employee Performance In The Regent Office of Majene District, West Sulawesi Province - Abdul Wahid Kamma (International Journal of Education, Information Technology, and Others, 2020)
This study aims to analyze the significant relationship between the independent variable and the dependent variable with the number of respondents as many as 75 people, respondents were taken randomly from the population at the Regent's Office of Majene Regency, the method used in measuring the level of relationship between the two variables is very much determined by how the employee's performance. which is in the research location which is known through the results of the respondents' answers that have been distributed using a questionnaire measuring tool which is a reflection of the problems found by researchers in the research location. Primary data processing uses theFormula Moment Product Correlation then to test whether the two variables have a significant relationship, the testing technique uses the t-test, as well as proving whether the validity of the hypothesis is accepted or rejected. The results showed that after all data were entered into theformula, it product moment correlation showed that the value of r person was 0.758, this indicated that the two variables had a strong relationship with the category. Then to test the significance of the relationship between these two variables, the correlation result is 0.758 compared to the r table value of 0.296 (0.758 ≥ 0.296), this implies that the two variables have a strong and significant relationship, so it can be said that the pattern of human resource development at the Regent's Office Majene Regency is quite good and this also affects the performance of employees at the institution.